Impact of E-commerce platforms on sales turnover among retail stores in Divisoria, Manila - Troy Jefferson G. Alvarado, Crystal Gayle G. De Castro, Sophia Izabelle B. Formalejo, Robe Stifencyril M. Ledesma, Kyla Catrina S. Matuguina, Karl Christian G. Roque 4 0 16; 5
ABSTRACT: The study looks into the relationship between E-commerce platforms and retail stores sales turnover in Divisoria, Manila. Its main goal is to conduct a thorough evaluation of the ways in which different E-commerce platforms impact the effectiveness and control of sales turnover in this dynamic district's retail environment. The goal of the study is to provide a comprehensive understanding of the transformative effects on business operations by analyzing complex relationships between these platforms and overall efficiency. The study shows that most respondents agree that e-commerce platform efficiency has a significant impact on retail sales turnover in terms of convenience and service quality. It demonstrates that the degree of perceived impact rises in tandem with the number of store years. It demonstrates that the degree of perceived impact is rising along with the variety of stores and e-commerce platforms. It is possible to conclude that there is a strong direct relationship between the two variables mentioned. This will give local businesses tactical advantage in enhancing productivity and management techniques in the dynamic retail industry. Keywords: E-commerce Platforms, Retailers, Sales Turnover, Efficiency, Service Quality, Convenience, Business Process Management, Marketing Strategies
Business Research: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2